NARRATIVE CONSTRUCTION AND ITS SOCIAL VITALITY (Margalla Papers, 2020)
Resilient narrative construction confines to the prevalence and function of Ideolog-based conflicts. While robust coordination and substantial enforcement strategies enhance the social vitality of narrative to bring about the desired social change. This article seeks to explore the narrative construction and its social vitality in the context of conflict and societal development. New narrative theoretical discoursereveals that deliberate narrative construction concentrates on individuals and society to redirect them in accordance with the wishes of narrative mentors. The conflict engendering elements like containment, self-identification of the individuals, and social positioning are, thus, subordinated to the narrative. This paper while using the narratological framework is looking at the phenomenon of socio-anthropological change from the perspective of narratology. The study could be of importance to students of low-intensity conflicts and militancy, especially corresponding to terrorism. The paper concludes that this new outlook of narrative has enlarged its scope beyond the corridors of literature into the renewed field of social narratology with an immense bearing on human behavior and attitudes. Bibliography EntryShah, Qasim Ali, Bahadar Nawab, and Arifullah Khan. 2020. "Narrative Construction and Its Social Vitality." Margalla Papers 24 (1): 147-157.